Analysis of the Time Series Generated by a New High-Dimensional Discrete Chaotic System. (27th August 2018) - Wang, Chuanfu; Fan, Chunlei; Feng, Kai; Huang, Xin; Ding, Qun
Abstract : The chaotic behavior of low-dimensional digital chaotic systems is seriously degraded, and the output sequence has a short period. In this study, a digital sequence generator based on a high-dimensional chaotic system is proposed to ensure performance and security. The proposed generator has low resource consumption, and the digital pseudo-random output sequence has a large period. To avoid the nonchaotic state, the multistability in the high-dimensional discrete chaotic system is analyzed. The statistical performance of the output sequence of the proposed digital high-dimensional chaotic system is evaluated, and the results demonstrate that it is a suitable candidate for a long-period pseudo-random sequence generator.